Sulphide stress cracking of a valve stem of duplex stainless steel. (December 2018) - Chandra, K.; Singh, A.P.; Kain, Vivekanand; Kumar, Niraj
Abstract: The present paper describes a failure investigation of a double disc valve stem made of duplex stainless steel 329 (UNS S32900). The valve stem which operated in moist H2 S environment at 128 °C in a heavy water plant had undergone cracking during operation. The microstructure of the stem material showed precipitates of σ-phase at ferrite/austenite boundaries and elongated oxide inclusions. The formation of σ-phase had occurred during the manufacturing stage of the stem. The crack propagation was more favourable in the ferrite phase and along the ferrite/austenite boundaries where precipitates of σ-phase were formed. It was concluded that the valve stem failed by sulphide stress cracking due to hydrogen embrittlement of ferrite phase. Recommendations to avoid such failures are also suggested. Highlights: An investigation of cracking of a valve stem of duplex stainless steel is described. The stem operated in moist H2 S environment at 128 °C in a heavy water plant. Stem material contained σ-phase which had formed during the manufacturing stage. Crack propagation was more favourable in ferrite and where σ-phase was present. Stem failed by sulphide stress cracking due to hydrogen embrittlement of ferrite.